Ketosis and migraine: a systematic review of the literature and meta-analysis - Neri, Lenycia de Cassya Lopes; Ferraris, Cinzia; Catalano, Guido; Guglielmetti, Monica; Pasca, Ludovica; Pezzotti, Elena; Carpani, Adriana; Tagliabue, Anna (Frontiers in Nutrition, 2023)
Introduction: Headaches are a prevalent disorder worldwide, and there is compelling evidence that certain dietary interventions could provide relief from attacks. One promising approach is the ketogenic therapy, which replaces the brain's fuel source from glucose to ketone bodies, potentially reducing the frequency or severity of headaches. Aim: This paper aims to conduct a systematic review of the scientific literature on the impact of ketosis on migraine, using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Results: After a careful selection process and bias evaluation, ten articles were included in the review, primarily from Italy. The bias assessment indicated that 50% of the selected articles had a low risk of bias in all domains, with the randomization process being the most problematic domain. Unfortunately, the evaluation of ketosis was inconsistent between articles, with some assessing ketonuria, some assessing ketonemia, and some not assessing ketosis levels at all. Therefore, no association could be made between the level of ketosis and the prevention or reduction of migraine attacks. The ketogenic therapies tested in migraine treatment included Very low Calorie Ketogenic Diet (VLCKD, n=4), Modified Atkins Diet (MAD, n=3), Classic Ketogenic Diet (cKDT, n=2) and the administration of exogenous source of beta-hydroxybutyrate (BHB). The meta-analysis, despite reporting high heterogeneity, found that all interventions had an overall significant effect (Z=9.07, p<0.00001; subgroup differences: Chi2= 9.19, dif=3, p=0.03, I2: 67.4%), regardless of the type of endogenous or exogenous induction of ketosis. Conclusion: The initial findings of this study suggest that metabolic ketogenic therapy may provide some benefit in treating migraines and encourage further studies, especially randomized clinical trials with appropriate and standardized methodology. The review strongly recommends the use of adequate measurement of ketone levels during ketogenic therapy to monitor adherence to the treatment and improve knowledge of the relationship between ketone bodies and efficacy.